2023
DOI: 10.1177/01427237231167301
|View full text |Cite
|
Sign up to set email alerts
|

Internal consistency and concurrent validity of the parental report instrument on language in pre-school-aged children – The Finnish Communicative Development Inventory III

Abstract: Few studies provide information on the reliability and validity of parental report instruments when assessing the language skills of pre-school–aged children. This study investigates the internal consistency and concurrent validity of the parental report instrument, the Finnish version of the Communicative Development Inventory III (FinCDI III), in children aged between 2;6 and 4;2 years (years;months, N = 155). One main aim was to analyze the validity of the information that parents can provide on different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Studies exploring gender-based differences in emerging language skills have commonly reported girls scoring consistently better than boys (Bornstein et al, 2004; Eriksson et al, 2012; T. Helland et al, 2017; Nouraey et al, 2021; Stolt, 2023). However, studies focusing on the role of gender in pragmatic ability are sparse and mixed findings are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring gender-based differences in emerging language skills have commonly reported girls scoring consistently better than boys (Bornstein et al, 2004; Eriksson et al, 2012; T. Helland et al, 2017; Nouraey et al, 2021; Stolt, 2023). However, studies focusing on the role of gender in pragmatic ability are sparse and mixed findings are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Different forms of CDIs can be used to assess children's early language development, including vocabulary comprehension, production, gestures, and grammar (for a review, see Law and Roy, 2008). A tool for slightly older children between 2;6 and 4 years is also available: the CDI III (Eriksson, 2017;Eriksson and Myrberg, 2023;Marchman et al, 2023;Stolt, 2023). The CDIs have been initially developed in American English.…”
Section: Introductionmentioning
confidence: 99%
“…After conducting a validation and norming study, Eriksson (2017 , p. 652) concluded that the structure of the Swedish version of the CDI-III could “well be integrated in similar instruments designed for other languages and cultures,” and CDI-III adaptations based on the Swedish version have since been developed for several new languages: Norwegian ( Garmann et al, 2019 ), Polish, Finnish ( Stolt, 2023 ), Estonian ( Tulviste and Schults, 2020 ), (Mexican) Spanish ( Jackson-Maldonado et al, 2022 ), and most recently Ukrainian. Both the Estonian version and the Norwegian one are based directly on the Swedish approach and mostly use the same categories as Eriksson (2017) , while still being adaptations, not translations.…”
Section: Introductionmentioning
confidence: 99%
“…b As discussed in sections 1.1.1–1.1.3, Eriksson (2017) combines his two grammar/syntax scales into one Swedish grammar score, while Tulviste and Schults (2020) and the current paper treat them as two separate scales for Estonian and Norwegian, respectively. c Stolt (2023) combines the two Finnish grammar scales Morphology and Language complexity with Phonology to a Language structures score (range: 0–43).…”
Section: Introductionmentioning
confidence: 99%